A midsummer night’s dream: Shakespeare appropriated in 60 minutes - Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2013)
A Midsummer Night’s Dream: Shakespeare Appropriated in 60 Minutes is, hopefully, the first of many future editions of the same venture. For anyone who is interested to stage the Bard’s plays but feels that getting started is a tremendous challenge, this book could serve as a useful guide. As Shakespeare’s plays are generally known to be too long and complex with an intermingling of sometimes incomprehensible language styles, this fuide offers a fresh take in performing his works, especially in this part of the world. Termed as an appropriation rather than adaptation, this guide will allow more freedom for the novice as well as experienced actors to ‘play the plays’ with confidence, understanding and most importantly, fun! Exclusive illustrations from an actual production, managerial worksheets and notes as well as the script used for the 60-minutes performance are included as ready-made references which can be adapted for any Shakespearean production.